Pengaruh Jumlah Kunjungan Wisatawan Terhadap Pajak Hiburan, Pajak Hotel, Pajak Restoran dan Pendapatan Asli Daerah Kota Bandung Tahun 2005-2012 - Nugraha, Nugraha; Purnamasari, Rita (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2014)
This study intended to analyze and provide empirical evidence about the influence of one of the factors that can affect the reception area of the tourism sector which is the number of tourist arrivals to the Entertainment Tax, Taxes,Tax and Revenue Regional Restaurant. Sources of data used in this study are the financial statements of Bandung in the period 2005-2012 were obtained from the Department of Tax and tourist traffic data obtained from the Department of Culture and Tourism of the city of Bandung. The design of this study used descriptive and explanatory nature of the causality method to determine the influence. By using the product moment correlation analysis. The results showed that the number of travelers is positive and it has significant effect to the Entertainment Tax of 63.8%, amounting to 64.6% hotel tax, restaurant tax of 80.4%, and revenue regional (PAD) of 52.9%. Government of Bandung city is required to continue to explore and manage the tourism potential held in an effort to increase tourist arrivals. Because the tourism industry is one sector that is reliable for the reception area